Answer:
x = -6
y = 1
Step-by-step explanation:
Elimination is a process in solving the system of the two unknowns.
It consists of subtracting or adding two equations in order to cancel out one of the unknowns.
In this case:
3x + 9y = -9
-3x + 8y = 26
we see that we can eliminate 3x and -3x by adding them up. 3x and -3x will cancel each other out and give 0 so we will be left with only y.
So, when we add them up, we get:
3x + 9y + (-3x) + 8y = -9 + 26
17y = 17
y = 1
Now that we know the value of y, we can plug it back into any of the two equations to find x:
3x + 9y = -9
3x + 9 = -9
3x = -18
x = -6